Interpasywny i ideologiczny wymiar polityki dziedzictwa kulturowego - Rauszer, Michał (Studia Etnologiczne i Antropologiczne, 2012)
A basic question that should be answered in the context of cultural heritage concerns its reinforcement in a social practice in line with all political implications. In view of the collapse of great narrations and a postmodernist distance of any engagement, directing towards an „identity constantly built”, the only form of a real engagement is cynical distance. The same is true of characters created for the purposes of a virtual game; their emotions are not simply false, but on the contrary, they sometimes reflect the state of their creators. At the same time, a virtual reality allows for maintaining a minimum of a distance thanks to the fact that we can withdraw from it any time we want. This distance is crucial when it comes to shaping a cultural identity these days. When we look at the functioning of local societies wielding power over an identity discourse of a community, two relationships appear. The first one consists in the functioning of regional societies in a social practice as original disponent of memory and identity. The second describes the attitude to societies of remaining inhabitants who, due to transferring the pleasure of awareness of their subjectivity to a local organization can deal with other issues. The very relationship is known as interpassivity. Political and ideological implications of both of them have been traced on the basis of Nie wszystko jest oczywiste, a book by Czesław Robotycki. A theoretician should notice here two important political reservations. Firstly, transferring of the pleasure of one’s own awareness is accompanied by the renouncement of making decisions on its shape so even though we convince ourselves that we are independent subjects (a cynical distance), in a social practice, objectively speaking, we behave as if we believed because of some “other” (local organizations). Secondly, building a local identity must be based on a tough theoretical basis because otherwise it will boil down to just folklore curiosities and ethnographic relics (though, in a conscious politics they are very important). The aim of my considerations is, thus, the evaluation of something that is as enigmatic as a cultural heritage in the context of modernity, and showing political dangers in the renouncement of one’s own subjectivity.